Local human capital externalities and wages at the firm level: the case of Italian manufacturing - Massimiliano Bratti; Roberto Leombruni (Institute for the Study of Labor (IZA), 2009)
We use a unique firm-level data set merging administrative information on average wages paid by firms by skill level (blue collars and white collars), Population Census information on the local stock of human capital available to firms and survey information on firm characteristics to investigate the existence and magnitude of local human capital externalities in Italian Manufacturing. The latter represents an interesting case study due to the prevalence of small family business and a technological lag with respect to the US, to which most evidence supporting local human capital spillovers refers. Our estimates show that in Italy, like in the US, firms located in geographical areas with a higher stock of human capital pay higher wages. This evidence is robust to many variants of the econometric specification and to addressing potential endogeneity issues using instrumental variables estimation and instruments based on the lagged expansion of the Italian higher education system and the lagged demographic structure.
Keywords: J24; J31; I20; 330; Firm; local human capital externalities; Italy; manufacturing; wages; Verarbeitendes Gewerbe; Regionaler Arbeitsmarkt; Humankapital; Spillover-Effekt; Lohnstruktur; Qualifikation; Klein- und Mittelunternehmen; Italien